SUCCESSFUL ORTHOTOPIC CARDIAC TRANSPLANTATION IN MULTI-SPECIALTY HOSPITAL (a clinical case) - K. V. Agapov; V. V. Vitsukaev; A. A. Shutov; A. G. Zakharchenko; O. A. Kurilova; Ya. P. Kireev (Вестник анестезиологии и реаниматологии)
The mortality rate reaches 50% in the patients with a terminal cardiac failure within one year after it is diagnosed. Orthotopic cardiac transplantation is a radical method to solve this problem and enhance life quality of such patients. Even 10 years ago this surgery and the most important post-transplantation management could be performed only by leading research centers. Currently, given the improvement and accessibility of cardiac surgery, anesthesiology, intensive care, cardiology, and immunology, this type of surgery and post-transplantation management have been mastered by multi-specialty regional centers. The latter improves the accessibility of high tech care for people residing in the periphery.